Prognostic significance of snail expression in hilar cholangiocarcinoma - Kong,Dalu (2012)
Many patients with hilar cholangiocarcinoma (HC) have a poor prognosis. Snail, a transcription factor and E-cadherin repressor, is a novel prognostic factor in many cancers. The aim of this study was to evaluate the relationship between snail and E-cadherin protein expression and the prognostic significance of snail expression in HC. We examined the protein expression of snail and E-cadherin in HC tissues from 47 patients (22 males and 25 females, mean age 61.2 years) using immunohistochemistry and RT-PCR. Proliferation rate was also evaluated in the same cases by the MIB1 index. High, low and negative snail protein expression was recorded in 18 (38%), 17 (36%), and 12 (26%) cases, respectively, and 40.4% (19/47) cases showed reduced E-cadherin protein expression in HC samples. No significant correlation was found between snail and E-cadherin protein expression levels (P = 0.056). No significant correlation was found between snail protein expression levels and gender, age, tumor grade, vascular or perineural invasion, nodal metastasis and invasion, or proliferative index. Cancer samples with positive snail protein expression were associated with poor survival compared with the negative expresser groups. Kaplan-Meier curves comparing different snail protein expression levels to survival showed highly significant separation (P < 0.0001, log-rank test). With multivariate analysis, only snail protein expression among all parameters was found to influence survival (P = 0.0003). We suggest that snail expression levels can predict poor survival regardless of pathological features and tumor proliferation. Immunohistochemical detection of snail protein expression levels in routine sections may provide the first biological prognostic marker.